Lies, media integrity and the new digital environment [Review] - Robie, D (Pacific Media Centre, School of Communication Studies, AUT University, 2014)
When Rachel Buchanan penned a commissioned article entitled ‘From the classroom to the scrapheap’ for The Age last September, she railed against Australian journalism schools, in particular, against an alleged ‘lie’ and ‘little integrity’ of journalism education. ‘Between 2002 and 2012, enrolments in journalism degrees almost doubled,’ she noted about what was troubling her across the Tasman. ‘We now have the bizarre situation where there are more people studying journalism than there are working journalists.’
Keywords: Media analysis; Digital media; Journalism education; Journalism history; Newspaper publishing